Memahami Hakikat Kebijakan Pengelolaan Satuan Pendidikan Dasar - Doni Aizus Idris; Jon Hendri; Tuti Susanti; Weni Hamdina; Hafiz (CV. Aksara Global, 2024)
Basic education is a critical phase in the formation of the foundation of knowledge, skills and values for each individual. The management policy of basic education units is central to ensuring equitable access and quality of education. This article explores the nature of basic education management policies, from the philosophical foundation to the implementation process. The library study method is used to analyze various related literature and policy documents, providing an overview of the historical evolution of basic education management from pre-modern times to the contemporary era. The results illustrate the complexities and challenges in policy planning, implementation and evaluation, as well as the importance of effective supervision. It is hoped that this in-depth understanding can improve the effectiveness of basic education policy and management globally.